Extraction, identification, and quantification of bioactive compounds from globe artichoke (Cynara cardunculus var. scolymus) - El-Hadidy, Gamal S.; Elmeshad, Walaa; Abdelgaleel, Mohammed; Ali, Mostafa (Penerbit Universiti Kebangsaan Malaysia, 2022)
This study looked at the best conditions for extracting bioactive compounds from globe artichoke (Cynara cardunculus var. scolymus), such as total phenolics, flavonoids, ascorbic acid, and inulin. The obtained results showed that the optimum conditions for extraction of total phenolics and flavonoids from receptacle and bracts of artichoke, when applying maceration at room temperature, with 70% methanol for 4 h. Genstin was the major phenolic compound (57.86 and 25.6 mg/100 g DM) in artichoke receptacle and bracts, respectively. The highest content of ascorbic acid extracted from artichoke parts was obtained using 1% citric acid solution at 25 °C. In addition, the optimum conditions for extraction of inulin were autoclave at 120 °C for 15 min. The most abundant essential amino acids were aromatic amino acids (phenylalanine and tyrosine), followed by valine, lysine, and leucine but sulfur amino acids were the limited amino acids found in the artichoke parts. Our results also suggested that bioactive compounds from artichoke extracts might have a promising future in the management of oxidative stress on the gastrointestinal tract and recommended as an attractive ingredient for developing functional food.